SUSTAINABLE PRACTICES IN BUSINESS: BEYOND CORPORATE SOCIAL RESPONSIBILITY - Dusmatov Begmuhammad Olimjonovich; Halilov Davlat Ikrom oʻg’li (Web of Journals Publishing, 2024)
Sustainable practices in business have evolved beyond traditional corporate social responsibility (CSR) initiatives to encompass broader strategies that integrate environmental, social, and economic considerations into core business operations. This article explores the shifting landscape of sustainability in business, highlighting innovative approaches and best practices for organizations seeking to embed sustainability into their DNA. It examines the importance of sustainable supply chain management, circular economy principles, and stakeholder engagement in driving meaningful change. Additionally, it discusses the role of technology, data analytics, and transparency in enhancing sustainability performance and fostering accountability. By embracing sustainable practices beyond CSR, organizations can not only mitigate risks and reduce environmental impacts but also unlock new opportunities for innovation, growth, and long-term value creation.
Keywords: sustainable practices, business sustainability, corporate social responsibility, sustainable supply chain management, circular economy, stakeholder engagement, technology, data analytics, transparency, innovation.